Genetic Control of B Cell Activation by Bacterial Lipopolysaccharide Is Mediated by Multiple Distinct Genes or Alleles - L. Michael Glodé; David L. Rosenstreich (1976)
Abstract Eleven closely related C3H mouse strains were examined for differences in their DNA synthetic response to a highly discriminatory endotoxin, LPS Escherichia coli K-235. Strains of the C3H line were found to be either high, intermediate, or low responders to endotoxin. Three stains, C3H/St, C3H/Bi, and C3H/CR were high responders. Six strains, C3H/He, C3HfB/He, C3H/Hen, C3Heb/Fej, C3H/DiSn, and C3H/Avy were intermediate responders, suggesting that a mutation producing decreased LPS responsiveness occurred in the C3H/He(C3H/An) strain between 1931 and 1945. Two strains, C3H/HeJ and C3H/Bts were unresponsive due to a mutation that occurred between 1960 and 1968. Breeding experiments among high, intermediate, and low responding strains documented probable codominant genetic control by the genes or alleles in the C3H/HeN and C3H/HeJ strains. In the C3H/HeN × C3H/St cross, dominance of the C3H/St gene over the C3H/He gene was documented, whereas the C3H/HeJ × C3H/St cross indicated codominance of these two genes. These findings may represent either three alleles or three distinct genes in C3H mice. A second X-linked gene locus was documented in the CBA/N strain which also causes impaired B cell responsiveness to LPS E. coli K235 in serum-free conditions. The abnormal gene products in the CBA/N and C3H/HeJ strains exhibit complementarity since F1 female animals from the cross between these two unresponsive strains are responsive to LPS. We conclude that there is at least one distinct X-linked gene locus and either three additional autosomal genes or three possible alleles at one or more autosomal loci which determine the LPS sensitivity of murine B cells.